The Nutri-Score nutrition label - Hercberg, Serge (2021)
Nutri-Score is a front-of-pack nutrition label with summary graded colour-coding, which aims to inform consumers, in a simple and understandable way, of the overall nutritional value of foods, in order to help them to make healthier choices at the point of purchase and to encourage manufacturers to improve the nutritional quality of their products. It is based on a five-colour scale (from dark green to dark orange) associated with letters, from A to E, to optimize logo accessibility and understanding by the consumer. Nutri-Score does not merely characterize foods as “healthy” or “unhealthy”. Rather, the graded logo provides semi-quantitative information, depending on the colour/ letter, of the relative overall nutritional composition of a food product compared to other similar products as to whether it is more or less favourable to health. Nutri-Score is the only proposed labelling scheme that adheres entirely to the concepts and processes that were published by the World Health Organisation (WHO) Europe concerning the validation studies that are required to select and evaluate a front-of-pack nutrition label. The aim of the present paper is to present the scientific basis for the design of the Nutri-Score and to summarize the various studies to validate its calculation method and its graphic format. We explore its effectiveness and superiority compared to other labelling schemes that have been implemented in other countries or supported by pressure groups. The necessity for objective, impartial consideration of how best to use Nutri-Score and avoid misunderstandings is highlighted.